Faktor Faktor Yang Mempengaruhi Produksi Jagung Di Desa Raraatean Kecamatan Tompaso Baru Kebupaten Minahasa Selatan - Rampengan, Gratcia; Mandei, Juliana Ruth; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2023)
This research aims to analyze the influence of independent variables, namely land area, capital, seeds, fertilizer and number of workers on the dependent variable on corn production results in Raraatean Village, Tompaso Baru District. This research lasted for 2 months, starting from February to March 2023. The data used was primary data obtained through direct interviews with corn farmers based on a list of questions, and secondary data obtained from related agencies such as village offices, scientific papers, journals, or theses. The results of this research are the influence of the independent variables on the dependent variable on production results based on the land area t test showing that there is an influence between land area and production, for seeds it shows that there is a positive and significant influence between seeds and production, for fertilizer it shows that there is no positive influence and significant between fertilizer and production and labor shows that there is a positive and significant influence between labor and production, while the simultaneous influence for the variables of land area, seeds, fertilizer and labor shows that there is a joint positive and significant influence between farming production with land area, seeds, fertilizer and labor and for business scale, it shows that the scale of corn farming reaches the Increasing Return To Scale (IRS) criteria.